1986
DOI: 10.1159/000100125
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation in Multiple Sclerosis

Abstract: Forty-nine multiple sclerosis patients with bladder symptoms and/or walking disability were subjected to a therapeutic trial with electrical spinal cord stimulation and transcutaneous electrical stimulation, a second aim being to compare these two treatments. A clear subjective improvement in bladder symptoms was achieved in the majority of the cases, and this was substantiated by objective parameters. In a proportion of cases a more moderate improvement seems to have been achieved in a variety of symptoms. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In these studies, the researchers hypothesized that utilization of TENS in thirty minute or more increments over a prolonged period of time may prove to limit the amount of knee spasticity and possibly result in enhanced motor function [16]. It was also observed that the implementation of TENS treatment has the capability to improve the knee flexion torque of those with multiple sclerosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the researchers hypothesized that utilization of TENS in thirty minute or more increments over a prolonged period of time may prove to limit the amount of knee spasticity and possibly result in enhanced motor function [16]. It was also observed that the implementation of TENS treatment has the capability to improve the knee flexion torque of those with multiple sclerosis [17].…”
Section: Introductionmentioning
confidence: 99%